Sugar in the social life of medieval islam - Satō, Tsugitaka, 1942- (Islamic Area Studies, 2015)
In Sugar in the Social Life of Medieval Islam Tsugitaka Sato explores the actual day-to-day life in medieval Muslim societies through different aspects of sugar. Drawing from a wealth of historical sources - chronicles, geographies, travel accounts, biographies, medical and pharmacological texts, and more - he describes sugarcane cultivation, sugar production, the sugar trade, and sugar's use as a sweetener, a medicine, and a symbol of power. He gives us a new perspective on the history of the Middle East, as well as the history of sugar across the world. This book is a posthumous work by a leading scholar of Middle Eastern and Islamic studies in Japan who made many contributions to this field.